Collective and creative consortia: combining knowledge, ways of knowing and praxis. Issue 2 (3rd May 2020) - Lawrence, Roderick J.
ABSTRACT: This paper is a think piece about planning and constructing built environments and infrastructure for healthy cities and communities founded on combinations of different types of knowledge and ways of knowing that include creative thinking. Hence, different disciplinary skills and competences should be interrelated, synthesized and applied creatively in complementary ways during concerted action between consortia of researchers, practitioners and representatives of civil society. Disciplines and professions should recognize the necessity of collective thinking that creatively combines knowledge, skills and competences in novel ways that respond to persistent problems in cities harmful to planetary health and human well-being. The paper discusses the dialectical and virtuous relations between discipline-based knowledge, profession-based know-how, and the ways of knowing of citizens. Then it advocates a mutual exchange between different types knowledge and ways of knowing by transdisciplinary contributions, because they enable a shared understanding of a problematic situation before it is changed. Creative and imaginative thinking are necessary to synthesize different types of knowledge and ways of knowing. This kind of contribution is illustrated by two large urban projects: the community-led Ringland Project for road traffic in Antwerp, Belgium, and the co-creation of a new housing cooperative in Zurich, Switzerland. Both projects have direct and indirect impacts on health.